Los Angeles Dodgers 5 vs Atlanta Braves 2 at Dodger Stadium - Watkins, Howard::::::::: (1987)
Albert Watkins, Adam Watkins wearing baseball glove and Howard Watkins standing by centerfield wall with Dodger Stadium in background Viewed from centerfield